Nontuberculous Mycobacteria Prevalence in Bats’ Guano from Caves and Attics of Buildings Studied by Culture and qPCR Examinations - Ivo Pavlik (MDPI AG, 2021)
A total of 281 guano samples were collected from caves (N = 181) in eight European countries (Bulgaria, Czech Republic, France, Hungary, Italy, Romania, Slovakia and Slovenia) and attics in the Czech R. (N = 100). The correlation of detection of mycobacteria between Ziehl–Neelsen (ZN) microscopy and culture examination and qPCR was strong. ZN microscopy was positive in guano from caves (58.6%) more than double than positivity in guano from attics (21.0%; p < 0.01). From 89 mycobacterial isolates (73 isolates from cave guano and 16 isolates from attics’ guano), 68 (76.4%) isolates of 19 sp., ssp. and complex were identified as members of three Groups (M. fortuitum, M.chelonae, and M. mucogenicum) and four complexes (M. avium, M. terrae, M.vaccae, and M.smegmatis). A total of 20 isolates (22.5%) belonged to risk group 1 (environmental saprophytes), 48 isolates (53.9%) belonged to risk group 2 (potential pathogens), and none of the isolates belonged to risk group 3 (obligatory pathogens). When comparing bat guano collected from caves and attics, differences (p < 0.01; Mann–Whitney test) were observed for the electrical conductivity, total carbon, total organic, and total inorganic carbon. No difference (p > 0.05; Mann–Whitney test) was found for pH and oxidation-reduction potential parameters.